Clonal conservation at the CGIAR genebanks: Example of Alliance of Bioversity International and CIAT - Panis, Bart (2025)
Conservation of crop genetic resources in genebanks is crucial for ensuring food security and agricultural sustainability. Genebanks store diverse crop varieties, preserving genetic traits that may be vital for future breeding, pest resistance, and climate adaptability. These genetic resources act as a safeguard against the loss of biodiversity, offering a valuable repository for recovering species affected by climate change, diseases, or disasters. By maintaining genetic diversity, genebanks support the development of resilient crops and contribute to the long-term stability of global food production systems